Iglesia de San Pedro, Klippan, Suecia : Sigurd, Lewerentz [1963-1966] - Isasi, Justo F. (2002)
Obra que se caracteriza por el uso del ladrillo
Keywords: ARQUITECTURA RELIGIOSA; IGLESIAS; KLIPPAN; SUECIA; SIGLO XX; HISTORIA; LADRILLO; CRITICA